2014
DOI: 10.1002/aenm.201400664
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Ordered Oxygen Defects on the Atomic Scale in Li2O2 for Li‐O2 Batteries

Abstract: The structure of the discharge product, Li2O2, in lithium‐oxygen batteries is revealed directly on the atomic scale. A unique stage ordering that the peroxide vacancy occupies preferentially in every other layer along the c‐axis of Li2O2 is observed. This finding provides new insight into the relationship between the structure of Li2O2 and the discharge/charge behavior of Li‐O2 batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 35 publications
4
30
0
Order By: Relevance
“…In contrast, as shown in Fig. 7b [51]. Impressively, when the batteries recharged to state III, HRTEM image (Fig.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…In contrast, as shown in Fig. 7b [51]. Impressively, when the batteries recharged to state III, HRTEM image (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…7a was acquired. It is interesting to observe the broadness peak in the EELS profiles, which is mainly related to the formation of Li 2−x O x as discharge products [51]. In contrast, as shown in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…We performed a STEM simulation on the Li 3 O 4 {1100} surface ([110] zone axis) and compared it with the measured STEM image reported by Xiao et al 45 . The simulation results are shown in Fig.…”
Section: Stem Simulationmentioning
confidence: 99%
“…In a recent work, Xiao et al [41] observed the presence of oxygen vacancy at the surface of discharged Li 2 O 2 using annular bright-field scanning transmission electron microscopy (ABF-STEM). The present oxygen vacancy provides another possibility to the charge transport along the surface of Li 2 O 2 , which could modify the transport of electron and ion.…”
Section: Charge Transportmentioning
confidence: 98%